2021
DOI: 10.1126/sciadv.abh0648
|View full text |Cite
|
Sign up to set email alerts
|

Analog memristive synapse based on topotactic phase transition for high-performance neuromorphic computing and neural network pruning

Abstract: Inspired by the human brain, nonvolatile memories (NVMs)–based neuromorphic computing emerges as a promising paradigm to build power-efficient computing hardware for artificial intelligence. However, existing NVMs still suffer from physically imperfect device characteristics. In this work, a topotactic phase transition random-access memory (TPT-RAM) with a unique diffusive nonvolatile dual mode based on SrCoOx is demonstrated. The reversible phase transition of SrCoOx is well controlled by oxygen ion migration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 55 publications
1
63
0
1
Order By: Relevance
“…Simultaneously, oxygen vacancies migrate to the LSM bottom electrode and then form the paths for oxygen ions by the external voltage, enabling the formation of the multiple filaments within the BM-SCO film to connect the top and bottom electrodes eventually, leading to the LRS. 43 As shown in the DFT calculation, the formation energy and the migration barrier along [001] direction of oxygen vacancies are noticeable higher for the BM-SCO film under compressive strain than those for the unstrained sample. In addition, Jalili et al 56 reported that the compressive strain can also enhance the oxygen vacancy formation energy in the LSM layer, making the oxygen ions more difficult to pull out from the LSM layer under compressive strain.…”
Section: Resultsmentioning
confidence: 68%
See 4 more Smart Citations
“…Simultaneously, oxygen vacancies migrate to the LSM bottom electrode and then form the paths for oxygen ions by the external voltage, enabling the formation of the multiple filaments within the BM-SCO film to connect the top and bottom electrodes eventually, leading to the LRS. 43 As shown in the DFT calculation, the formation energy and the migration barrier along [001] direction of oxygen vacancies are noticeable higher for the BM-SCO film under compressive strain than those for the unstrained sample. In addition, Jalili et al 56 reported that the compressive strain can also enhance the oxygen vacancy formation energy in the LSM layer, making the oxygen ions more difficult to pull out from the LSM layer under compressive strain.…”
Section: Resultsmentioning
confidence: 68%
“…In addition, both devices undergo a forming process at a negative voltage (see Figures S3 and S4 for details), consistent with those reported in some previous studies. 50,51 However, some other studies 41,43 reported a forming process with opposite polarity, i.e., positive forming. The possible origin for the different forming polarities is discussed in Figure S4.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations